2021
DOI: 10.2147/nss.s297856
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning for Diagnosis and Classification of Obstructive Sleep Apnea: A Nasal Airflow-Based Multi-Resolution Residual Network

Abstract: This study evaluated a novel approach for diagnosis and classification of obstructive sleep apnea (OSA), called Obstructive Sleep Apnea Smart System (OSASS), using residual networks and single-channel nasal pressure airflow signals. Methods: Data were collected from the sleep center of the First Affiliated Hospital, Sun Yat-sen University, and the Integrative Department of Guangdong Province Traditional Chinese Medical Hospital. We developed a new model called the multi-resolution residual network (Mr-ResNet) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Table 1 summarizes the different sleep study approaches followed by various researchers. PSG signals contain ECG, EEG, EMG, nasal sounds, and breathing patterns [ 6 , 21 , 35 ]. Figure 2 portrays the distribution of the signal source used in the literature.…”
Section: Signal Sourcementioning
confidence: 99%
“…Table 1 summarizes the different sleep study approaches followed by various researchers. PSG signals contain ECG, EEG, EMG, nasal sounds, and breathing patterns [ 6 , 21 , 35 ]. Figure 2 portrays the distribution of the signal source used in the literature.…”
Section: Signal Sourcementioning
confidence: 99%
“…Many studies have shown that a hybrid model has better performance than a specific classifier. This paper [32] has anticipated the Mr-ResNet framework using nasal pressure airflow signals for OSA and verified good feasibility for clinical application.…”
Section: Introductionmentioning
confidence: 77%
“…It was observed that automatic detection of sleep apnea can be performed reliably on clinical data too. [32] Automatic sleep apnea detection using LS SVM performs better although the study considered single-channel ECG but could not classify apnea and hypopnea. [33] The OSA detection using SpO2 is better than IHR from ECG according to the work.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, many studies have been conducted on the possibility of diagnosing SAS using breath sounds during sleep. Recently, studies using machine learning and AI have been reported [ 23 , 24 ].…”
Section: Sleep Apnea Syndrome (Sas) Researchmentioning
confidence: 99%
“…In another example, we used a continuous wavelet transform (CWT) to visualize breath sounds during sleep and to communicate the condition to the patient. CWT is a useful analysis method (considering time and frequency) and is expressed by Equation (1) [ 23 , 24 ]. …”
Section: Sleep Apnea Syndrome (Sas) Researchmentioning
confidence: 99%